Molecular Fluorescence Imaging Spectroscopy for Mapping Low Concentrations of Red Lake Pigments: Van Gogh's Painting The Olive Orchard. Issue 15 (11th February 2020) - Dooley, Kathryn A.; Chieli, Annalisa; Romani, Aldo; Legrand, Stijn; Miliani, Costanza; Janssens, Koen; Delaney, John K.
Abstract: Vincent van Gogh used fugitive red lake pigments that have faded in some paintings. Mapping their distribution is key to understanding how his paintings have changed with time. While red lake pigments can be identified from microsamples, in situ identification and mapping remain challenging. This paper explores the ability of molecular fluorescence imaging spectroscopy to identify and, more importantly, map residual non‐degraded red lakes. The high sensitivity of this method enabled identification of the emission spectra of eosin (tetrabromine fluorescein) lake mixed with lead or zinc white at lower concentrations than elemental X‐ray fluorescence (XRF) spectroscopy used on account of bromine. The molecular fluorescence mapping of residual eosin and two carmine red lakes in van Gogh's The Olive Orchard is demonstrated and compared with XRF imaging spectroscopy. The red lakes are consistent with the composition of paint tubes known to have been used by van Gogh. Abstract : Looking for eosin : In situ mapping of fugitive red lake pigments (eosin and carmine lakes) in a van Gogh painting was achieved with molecular fluorescence imaging spectroscopy. The high sensitivity of this method enabled lower concentrations of red lakes to be detected than by elemental X‐ray fluorescence imaging spectroscopy.